Nature of Evil in Macbeth - Islam, Md Saiful (Arts Faculty Journal, 2012)
It is a statement of evil (Knight 18). The Whole play may be writ down as a wrestling of destruction with creation (Knight 140). It contains the decisive orientation of Shakespearean good and evil (Traversi 86). The above statements serve to prove that Macbeth is Shakespeares most profound and mature vision of evil. In this play, Shakespeare presents the overspreading influence of evil over the guilty and ambitious minds which lead them to commit the most treacherous villainy that affect not only the man and the state, but the family and the physical universe as well. But this evil is not the one that finally triumphs, Shakespeare in this play also provides the essential morality and courage which in their progression defeat the evil and restore the natural order of things. This paper endeavors to present the various viewpoints from which this evil can be interpreted. It shows how Shakespeare has depicted the transformation of a good person to a ghastly figure. The effect of evil in Lady Macbeth is also analyzed. The paper also tries to examine whether this evil is purely psychological or has an exterior form. DOI: http://dx.doi.org/10.3329/afj.v4i0.12940 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.185-194